2004
DOI: 10.1111/j.1365-2524.2004.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among older people in Sweden receiving help from informal and/or formal helpers at home or in special accommodation

Abstract: The present study describes and compares quality of life (QoL) and factors which predict QoL among people aged 75 years and over who receive help with activities of daily living (ADLs) from formal and/or informal helpers. The subjects were living at home or in special accommodation in Sweden. A postal questionnaire was sent to a randomly selected and age-stratified sample of 8500 people. The response rate was 52.8% (n = 4337), and 1247 people [mean age (+/- SD) = 86.4 +/- 5.9 years] received help and indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 33 publications
4
48
0
6
Order By: Relevance
“…The samples that have been employed tend to be made up of more than 30 individuals, while more than half of the studies analyzed in this review 7,25,26,29,30,37,38,42 made use of representative samples. Thus, probabilistic selection of the elements to be studied within a determined temporal and geographical context was preferred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples that have been employed tend to be made up of more than 30 individuals, while more than half of the studies analyzed in this review 7,25,26,29,30,37,38,42 made use of representative samples. Thus, probabilistic selection of the elements to be studied within a determined temporal and geographical context was preferred.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, much of the literature indicates that larger networks are associated with greater well-being among the elderly population 21,23,[28][29][30] . It should be noted that, in general, the social networks of the elderly are small, and this may be associated with a low quality of life/well-being among these individuals.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It is also well known that limited ability to perform activities of daily living also means decreased life satisfaction. For instance, Hellström et al (2004) found among 448 Swedish people aged 75 and over with reduced ADL capacity that reporting several diseases and functional impairment determined low life satisfaction. Among people aged 65 and above (n = 1000) in Australia reporting themselves as being limited in the ability to perform instrumental activities of daily living, functional impairment was shown to mediate the relationship between diseases and well-being (Kendig et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…on the self-esteem of the subjects, which in turn lowered their general evaluation of quality of life [22]. in the international research conducted by Mozhan et al in 23 countries, in the opinion of 7401 elderly subjects, the key factors impacting evaluation of life quality included: ability to perform daily activities, good health, sensory fitness, mobility, freedom/independence, energy [23].…”
Section: Discussionmentioning
confidence: 99%